دراسة فطريات البياض الدقيقي Erysiphaceae على بعض نباتات الفصيلة الخيمية Umbelliferae في محافظة اللاذقية - علي, نوال (Latakia University Journal -Biological Sciences Series, 2018)
أظهرت الدراسة في بعض مناطق محافظة اللاذقية (خلال فصلي الربيع والصيف لعام 2005) إصابة /14/ عائلاً نباتياً من الفصيلة الخيمية Umbelliferae بثلاثة أنواع من فطريات البياض الدقيقي هي DC. Erysiphe heraclei, Leveillula lanuginosae (Fuck)Gdovin , Oidium sp. . سجل تواجد النوع E. heraclei على /12/ عائلاً نباتياً والنوع L. lanuginosae على عائل نباتي واحد, والنوع O.sp على عائل نباتي واحد . بينت النتائج تواجد النوعين الفطريين E. heraclei, L. lanuginosae بالطورين الكونيدي ( اللاجنسي ) والجنسي. أظهرت نتائج الدراسة سيادة النوع E. heraclei على النوعين L. lanuginosae وOidium sp.. The survey study was conducted in some regions of Lattakia during of spring and summer 2005 it showed that /14/ host plants were found to be infected with three fungi species of powdery mildews Erysiphe heraclei DC, Leveillula lanuginosae (Fuck) Gdovin and Oidium sp. The E. heraclei was recorded on /12/ host plants, L. lanuginosae on /1/ host plant and Oidium sp, on /1/ host plant. The results showed the existence of two fungi species E. heraclei and L. lanuginosea on both conidial and cleistothecial stages together with their all respective host plants. The results also showed that the E. heraclei was dominant on both the L. lanuginosae and Oidium sp. .